IDENTIFYING & PRIORITIZING THE BARRIERS ON EXECUTION OF COST MANAGEMENT - Souri, Farbod (The journal of contemporary issues in business and government, 2021)
The cost management is a system for planning and control of the costs for the creation of which there are numerous ways. Every organization shall adopt a more appropriate method with respect to their terms and conditions. The cost management assists in identification, gathering, classification and allocation of the information that are used in planning, control and decision-making, for keeping a desirable limit of the costs. Just like every other institutes, the Islamic Azad University requires an optimized use of the cost management to control and reduce its expenses. For this reason and with respect to the importance of the case, the present research has dealt with identifying and prioritizing the barriers on execution of the cost management in the Islamic Azad University. Enjoying the experts’ theories and by the means of a conducted questionnaire, using the structural equations, the result of the research data analysis indicated that the factor of “failure in accurate assessment of the performance of the chancellors of the university branches and regions” is the most important barrier in accurate management of the costs in Islamic Azad University. After that “unwillingness of the staff for economization, and for endeavor to decline the costs” included the highest level of factor loading in this case. It was also observed that the barrier of “ not paying attention to the liability assessment accounting system” is in the second place in raking of the executive barriers and after that “failure in benefiting from modern costing techniques” is in the next place. Furthermore, “failure in execution of appropriate encouraging and punishment policies”, “uncompetitiveness of the system and a weak demand for response”, “inexistence of a uniform culture of economization within the university’s environment”, and “not paying the required attention to the missed opportunity costs” are in the next places. Eventually the barriers of “not paying attention to the dedicated budget”, “not paying attention to the efficacy, effectiveness and economic efficiency of the organizational activities” and “the university’s dependence on the tuition incomes” are on the lower levels of importance from the viewpoint of the respondents.